THE HUMAN CAPITAL BLUEPRINT: ALIGNING HR STRATEGY WITH BUSINESS GOALS - Larasati Iman Syalsabillah; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
In an era of digital disruption, organizations face the critical challenge of aligning human capital with strategic business goals. This article introduces the Human Capital Blueprint as a transformative framework for bridging this gap, moving HR from administrative support to strategic value creation. Through the case study of StyleCraft, a traditional retailer undergoing digital transformation, we demonstrate how the blueprint enables organizations to translate business objectives into actionable talent strategies. The framework incorporates skills gap analysis, a balanced build-and-buy approach to talent acquisition, immersive learning programs, and metrics that directly link human capital investments to business outcomes. Findings reveal that successful transformation requires treating human capability development as a core business strategy rather than an HR initiative. The article provides leaders with a proven model for building an agile, future-ready workforce capable of driving sustainable competitive advantage in volatile markets.